WEB MINING AND ITS CATEGORIES – A SURVEY (International Journal of Engineering and Computer Science, 2017)
The World Wide Web’s constant growth and transformation offers great opportunities and poses many challenges for exploitation. The Web Mining has emerged as a possible answer to these challenges by offering an approach in organizing and sharing the Web, and explicitly considering user needs and requirements. Web mining is a very hot research topic which combines two of the activated research areas: Data Mining and World Wide Web. The Web mining research relates to several research communities such as Database, Information Retrieval and Artificial Intelligence. Web mining basically can be divided into three categories: Web Content mining, Web Structure mining and Web Usage mining, these three categories deal with different features of a web page. Web content mining deals with discovering useful information or knowledge from web page contents, web structure mining deals with discovering and modeling the link structure of web, web usage mining is used to discover interesting usage patterns from web data. For the survey, we focus on representation issues, on the process, on the learning algorithm, and on the application of the recent works as the criteria. We conclude the paper with some research issues